Tourist motivation to visit the Kilim Karst Geoforest Park in Langkawi Island, Kedah - Sulaiman, Muhammad Qayyum Alemilhadie (2016)
The issue of Langkawi is in danger of losing its Unesco Geopark status following the world body’s move to issue a “Yellow Card” warning because of the local authorities’ failure to abide by conservation and sustainable practice requirements. A study was conducted to determine tourist motivation to visit the Kilim Karst Geoforest Park in Langkawi Island, Kedah. This research also conducted to determine the push and pull factor of tourist to visit the Kilim Karst Geoforest Park. Factor such as family togetherness, self-exploration, convenience of facilities and key tourist and safety were used to identify the push and pull factors. This study also related the socio demographic background which is nationality, gender, age, marital status, ethnic, religion, education level, occupation and income. Two hundred respondents were interviewed using structured questionnaire. The data was collected between January until February 2016. Descriptive analysis and multiple regressions were used in analysing data. The result showed that the push factor was having fun with family and friends and the pull factor was tourism destination with attractive interpretive signage. From the visitor recommendation, the responsible party in this park should create more attractive interpretive signage to attract more visitors to visit the park.